Green Warriors Army Environmental Considerations for Contingency Operations from Planning Through Post-Conflict - Mosher, David E. (RAND Corporation, 2008)
This study assesses whether Army policy, doctrine, and guidance adequately address environmental activities in post-conflict phases of contingencies. A review of policy, doctrine, operational experience, and documentation, as well as interviews with Army personnel, indicates that environmental concerns can have significant impacts. Recommendations are made for improving the Army?s approach to environmental issues in contingency operations.